Trends and Developments in Fitness Test Research: A Scopus Bibliometric Analysis - Muhammad Dzikry Abdullah Al Ghazaly; Agung Hilmi Wahdi; Rifki Rosad; Mochamad Derry Prasaja; Nadila Maesara (Universitas Negeri Semarang, 2026)
The evaluation of physical fitness is a core element of sport science, clinical exercise physiology and population health surveillance but a comprehensive bibliometric synthesis of the recent global trend is missing. The present study aims to describe the productivity, intellectual structure, and thematic evolution of the research on fitness tests published between 2015 and 2026. A total of 5,766 peer-reviewed articles indexed in the Scopus database (Elsevier) were retrieved with the search string TITLE-ABS-KEY (